Effect of enzyme supplementation of broiler diets based on corn and soybeans - Zanella, I. [UNESP]; Sakomura, N. K. [UNESP]; Silversides, F. G.; Fiqueirdo, A. [UNESP]; Pack, M. (Poultry Science Assoc Inc, 1999)
Digestibility of diets based on corn and soybean meal or soybeans treated by roasting or extrusion, with or without an enzyme supplementation, was measured by true (Sibbald) methods, by analysis of excreta, and by analysis of ileal digesta. Only analysis of ileal digesta was able to consistently measure differences between soybean and enzyme treatments in the digestibility of CP, starch, fat, and ME. The amino acid (AA) digestibility of the diets was measured by analysis of the ileal contents. Whereas enzyme supplementation improved overall CP digestibility by 2.9%, this improvement was not equal for all AA. of the AA most important for broilers fed corn-soybean diets, the digestibilities of Lys, Met, and Arg were not improved or not improved significantly by the enzyme supplementation; however, that of Val was improved by 2.3% and that of Thr was improved by 3.0%. A performance trial demonstrated that enzyme supplementation with equal diet formulation improved BW and the feed conversion ratio by 1.9 and 2.2%, respectively. A second performance trial compared standard diet formulations with formulations using enzyme supplementation and energy levels that were reduced by the amount of improvement provided by the inclusion of enzyme in the first performance trial. No difference was seen between treatments, showing that the improvement of nutrient utilization brought about by enzyme supplementation completely compensated for the reduced energy content. Whereas enzyme supplementation should allow a reduction in CP formulation as well, individual AA were not improved equally by supplementation and should also be balanced.
Keywords: metabolizable energy; Amino acids; broiler; enzyme; corn-soybean diets